2016
DOI: 10.7326/m16-0361
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Health Outcomes of a Mediterranean Diet With No Restriction on Fat Intake

Abstract: Department of Veterans Affairs, Veterans Health Administration, Office of Research and Development, Quality Enhancement Research Initiative. (PROSPERO: CRD42015020262).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 106 publications
0
105
0
8
Order By: Relevance
“…5 A pooled analysis of nine cohort studies studying adherence to a Mediterranean diet showed a 9% reduction (95% CI for HR: 0.84–0.98) in colorectal cancer incidence for the highest vs. lowest quantile. 6 A systematic literature review of five case-control and seven cohort studies also supported the association between a higher overall diet quality, including Mediterranean diet score and HEI, and a lower risk of colorectal cancer, and suggested similar associations for men and women. 8 …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…5 A pooled analysis of nine cohort studies studying adherence to a Mediterranean diet showed a 9% reduction (95% CI for HR: 0.84–0.98) in colorectal cancer incidence for the highest vs. lowest quantile. 6 A systematic literature review of five case-control and seven cohort studies also supported the association between a higher overall diet quality, including Mediterranean diet score and HEI, and a lower risk of colorectal cancer, and suggested similar associations for men and women. 8 …”
Section: Discussionmentioning
confidence: 77%
“…13 Several indexes have been applied to evaluate the role of diet in various health outcomes. 46 Indeed, they have been associated with a lower risk of colorectal cancer, 710 the third most common cancer in the United States. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Diet may be another confounder. A high meat intake increases and a Mediterranean diet decreases both the risk of DM and of CRC [45]. …”
Section: Epidemiological Association Between Diabetes and Crcmentioning
confidence: 99%
“…The association between the MED and cancer focused on the most recent meta-analysis by Schwingshackl and colleagues 24 along with a review and analysis by Bloomfield and colleagues 38 and a meta-analysis focused on breast cancer by van den Brandt and colleagues. 39 Based on these three metaanalyses, greater conformance with a Mediterranean-style eating pattern was consistently found to be inversely associated with total cancer as well as site-specific cancers, including colorectal, breast, and prostate.…”
Section: Research Snapshotmentioning
confidence: 99%